Nanopartículas lipídicas baseadas em óleos essenciais com atividade contra espécies bacterianas isoladas de humanos - Silva, Elenice Francisco da (2023)
Bacterial resistance has become a public health concerning worldwide, due to the increase in multidrug-resistant bacterial species, such as: Acinetobacter baumannii, Klebsiella pneumoniae and Pseudomonas aeruginosa. Such bacteria are responsible for causing serious infections in hospitalized patients, which can progress to a generalized infection, sepsis and death. Bioactive compounds of natural origin, such as essential oils (EO), have been used by popular medicine for years, due to their intrinsic biological activities, representing a promising alternative for new treatments. Its encapsulation in nanostructured lipid carriers (NLC) can bring several benefits. The present study aimed to develop NLC formulations composed of EO and vegetable butter that present physicochemical stability, biocompatibility and in vitro activity against strains of A. baumannii, K. pneumoniae and P. aeruginosa isolated from humans. First, a screening of 14 natural oils was carried out by the disk diffusion test to select the most promising samples in terms of antibacterial activity. Thus, 4 EO were selected to be nanoencapsulated as active and structural compounds in the preparation of different NLC formulations. Then, 11 NLC were prepared and evaluated for physicochemical stability (particle size, polydispersion index and Zeta potential) for 1 year (25 °C). In vitro antimicrobial assay was performed to determine the minimum inhibitory concentration of each NLC against the tested strains. The most promising system was composed of cinnamon EO (NLC/CAN), and its structural properties were evaluated using experimental methodologies (Fourier transform infrared spectroscopy, differential scanning calorimetry and scanning electron microscopy). Finally, the in vivo nanotoxicity study was carried out through the alternative biological model of chicken embryo, which determined that NLC/CAN did not induce nanotoxicity in any of evaluated parameters.